Quantitative STEM imaging of electron beam induced mass loss of epoxy resin sections - Skoupy, Radim; Nebesarova, Jana; Slouf, Miroslav; Krzyzanek, Vladislav (Ultramicroscopy, 2019)
In sample preparation of biological samples for electron microscopy, many types of embedding media are widely used. Unfortunately, none of them is perfectly resistant to beam induced damage. The article is focused on mass loss measuring of pure epoxy resin EMbed 812 that replaced Epon - the most widely used embedding resin for biological electron microscopy, in a form of ultrathin sections with thicknesses ranging from 30 to 100 nm. The STEM imaging was performed in a quantitative way which allowed us to estimate the mass loss directly up to the total dose of 3000 e-/nm2. For data acquisition we used SEM equipped with a commercial STEM detector working at a relatively low acceleration voltage of 30 kV. In this study we estimated the influence of various factors which can affect the endurance of the epoxy resin EMbed 812 ultrathin sections under an electron beam, such as the sample aging, differences between storing the samples in forms of ultrathin sections and whole blocks, ultrathin sections thicknesses, temperature of the sample, probe current, and one or two-sided carbon coating of ultrathin sections. The aim of this work is to investigate beam induced mass loss at electron energies of SEM and find out how to reduce the mass loss.
Keywords: mikroskopie elektronová rastrovací transmisní; Microscopy, Electron, Scanning Transmission; epoxidové pryskyřice; Scanning transmission electron microscopy; Mass loss; Epoxy resin; elektrony; Scanning electron microscopy; Epoxy Resins; Electrons; EMbed 812 resin; Epon resin